A pedagogy for narrator actors: creative practices and strategies (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This paper presents epic-narrative strategies for theatrical performance, based on a teaching experience with the Actor Narrator curricular component in the Theater Degree course at the Federal Institute of Ceará (IFCE), a component whose program is inspired by Brecht's aesthetic-pedagogical project with learning plays. This text analyzes these strategies in two exercises focused on discovering principles for creating a community of actors as co-fabulators. As a third experience, the study of the adaptation of A Man’s A Man with students is reported, taking the text as a model of action, in order to reflect on a possible pedagogy for narrator actors.
Keywords: actor Narrator; epic-narrative practices; model action